[18F]FDG PET/CT role in FUO among patients with end-stage renal disease on renal replacement therapy - Domenico Albano; Chong Jiang; Francesco Bertagna (Annals of Nuclear Medicine, 2026)
Abstract Objective End-stage renal disease (ESRD) patients undergoing renal replacement therapy (RRT) are at increased risk of infections, inflammatory disorders, and malignancies because of immune dysfunction, repeated vascular access procedures, and immunosuppressive therapy after kidney transplantation. Fever of unknown origin (FUO) is particularly challenging to investigate in this population, and evidence regarding the role of [18 F]FDG PET/CT remains limited. This study evaluated the diagnostic performance, clinical impact, and predictors of positive [18 F]FDG PET/CT findings in ESRD patients with FUO. Methods This retrospective single-center study included ESRD patients receiving hemodialysis, peritoneal dialysis, or kidney transplantation who underwent [18 F]FDG PET/CT for FUO between 2014 and 2021. PET/CT findings were compared with the final diagnosis established by microbiological, histopathological, imaging, laboratory, and follow-up data. Sensitivity, specificity, predictive values, likelihood ratios, and diagnostic accuracy were calculated. Clinical impact was assessed according to the influence of PET/CT on diagnostic and therapeutic management. Results Eighty-seven patients were retrospectively included, 53 (61%) on hemodialysis, 27 (31%) on peritoneal dialysis, and 7 (8%) after kidney transplantation. [18 F]FDG PET/CT was positive in 57 cases (65%). Final diagnoses included infectious diseases in 36 patients, non-infectious inflammatory diseases in 20, malignancies in 10, while no diagnosis was established in 21. The most common infectious causes were catheter-related bloodstream infection, infective endocarditis, spondylodiscitis, pneumonia, and vascular graft infection; large-vessel vasculitis was the predominant inflammatory disease, and lymphoma the most frequent malignancy. PET/CT achieved a sensitivity of 77%, specificity of 71%, positive predictive value of 89.5%, negative predictive value of 50%, and overall accuracy of 76%. Elevated C-reactive protein, erythrocyte sedimentation rate, neutrophil-to-lymphocyte ratio, and longer hospitalization independently predicted positive PET/CT findings. PET/CT influenced clinical management in 66 patients (76%) by guiding targeted therapy, invasive diagnostic procedures, additional investigations, or avoiding unnecessary interventions after negative examinations. Conclusion [18 F]FDG PET/CT demonstrates good diagnostic accuracy and substantial clinical impact in ESRD patients with FUO receiving RRT. These findings support the early integration of PET/CT into the diagnostic work-up of this high-risk population, particularly in patients with elevated inflammatory biomarkers.